Impact of different culture conditions on growth and biopigments of Anacystis (Synechococcus) nidulans - Kulshreshtha, Jyoti; Kumar, Manoj; Singh, G P (The Indian Journal of Agricultural Sciences, 2012)
The present study makes a comparative investigation of different commercially important pigments in A. nidulans under different culture conditions. Temperature ranges, i e 25–29 °C and 29–36 °C were provided to the cultures under three different types of culture conditions, i e constant light, alternate light and dark condition (12:12) and natural day light condition. Cultures at temperature 29–36 °C receiving alternate light and dark period (12:12) showed maximum growth with biopigment accumulation and minimum was observed in constant light at 25–29 °C. Continuous protein synthesis in the dark at the expense of the stored carbohydrates might be the reason of high biliprotein and carotenoid synthesis which also increase its commercial and economic value. This proves alternate light and dark period (12:12) at 29–36 °C condition as a cost saving strategy for large scale production of biopigments.